Directions for improving the quality of tourism services - Algirdas Giedraitis; Rima Karsokienė (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
The authors (Langviniençe, 2014; Prentice, 2020; Grasso & Sergi, B.S. Eds., 2021) claim that over the past few decades, tourism has continuously expanded and strived to become one of the largest and fastest growing economic sectors in the world. Tourism is primarily a vital industry for the social and environmental development of local communities. Due to the influence of economic, social and political processes of globalization, tourism has become one of the leading industries in many countries.
Keywords: C83; 330; tourism; tourism service; tourist promotion